The construction process of pre-cast concrete piling / Syamimi Mohamad Suhaimy - Mohamad Suhaimy, Syamimi (Universiti Teknologi MARA UiTM,Perak, 2022)
Piling is the process of drilling foundations through the ground to provide more structural strength to the weak soil underneath. Piling is essential for high-rise buildings. This report is about to recognise the pre-cast concrete piling method. This report also covers pre-cast concrete piling installation, management, and other aspects of pre-cast concrete piling construction. Interviews are also utilised to go more into piling construction and project management. Several elements for piling construction were taken from Jack-In-Pile construction sites in Batu Kawan. These construction aspects included pile driving, machineries or piling rigs, welding of two-piece piles, and steel connection of two-piece piles. This pile construction should be recognised by every contractor and client in order to increase construction productivity. Last but not least, employees must complete their tasks on schedule. This is relevant to the building industry. Every client who makes a deposit to the developer or general contractor wishes their ideal home or building would be finished on schedule.